Culturally-rooted beliefs and learning exploring the relationships among social axioms, achievement goals, and learning strategies of Filipino college students - Bernardo, Allan B. I. (Philippine Journal of Psychology, 2004)
An exploratory study was undertaken to explore the relationships among (a) culturally-rooted social beliefs or social axioms, (b) achievement goal orientation, and (c) learning strategies of college students. Some 284 students in a private sectarian univesity in Southern Philippines were asked to inidcate their social beliefs using the Social Axiom Survey of Leung et. al. (2002), their goals in the Achievement Goal Questionnaire by Harackiewicz et.al. (1997, 2000), and the strategies they used in studying in the Motivated Strategies for Learning Questionnaire by Pintrich et. al. (1993). The results were analyzed using correlational analysis. The results indicated some expected trends consistent with hypotheses relating the specific nature of the social belief with the adoption of particular achievement goals and/or the use of particular learning strategies. However, many unexpected results suggest that there are still conceptual and theoretical gaps in how these three constructs are related. The results are discussed in terms of how the influence of socially-rooted beliefs on different psychological aspects of the educational experience may be studied further.